2008
DOI: 10.1080/15321810802569543
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response for L1, E6, E7 HPV 16, and HPV 18 Antigens in Tunisian Women with Cervical Cancer

Abstract: Results obtained in the present work indicated that the Luminex assay is more sensitive than ELISA. The reactivity to the early antigens E6 and E7 was 37% versus 42% for HPV 16 and 21% versus 20% for HPV 18 among cervical cancer cases using ELISA. However, these ratios were 44% and 61%, respectively, for E6 and E7 HPV 16 versus 28% and 21% for E6 and E7 HPV 18 when using the Luminex technique. Data also indicated that HPV 16 and HPV 18 showed distinct profiles for the different antigens tested. Finally, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Studies using a similar or alternative serological assays for E6 and E7 have also reported lack of seroconversion in a substantial fraction of cases. 3,4,[21][22][23][24][25][26][27][28][29][30][31][32][33] In a prospective study of cervical cancer, less than 10% of cervical cases were positive for antibodies to E6 and E7 proteins of HPV16 or 18, and an association with risk was only observed for cervical cancer diagnosed within 3.5 years, 42 suggesting that immune response to E6 and E7 occurs only late in the progression to malignancy. 33,47 This may be somewhat different to the picture for HPV-related oropharyngeal cancer, for which a recent nested case-control analysis reported that the detection of HPV16 E6 was strongly associated with the risk of subsequent oropharynx cancer more than 10 years before the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using a similar or alternative serological assays for E6 and E7 have also reported lack of seroconversion in a substantial fraction of cases. 3,4,[21][22][23][24][25][26][27][28][29][30][31][32][33] In a prospective study of cervical cancer, less than 10% of cervical cases were positive for antibodies to E6 and E7 proteins of HPV16 or 18, and an association with risk was only observed for cervical cancer diagnosed within 3.5 years, 42 suggesting that immune response to E6 and E7 occurs only late in the progression to malignancy. 33,47 This may be somewhat different to the picture for HPV-related oropharyngeal cancer, for which a recent nested case-control analysis reported that the detection of HPV16 E6 was strongly associated with the risk of subsequent oropharynx cancer more than 10 years before the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 The early HPV oncoproteins E6 and E7 interact with cellular proteins involved in cell cycle control and DNA repair, most notably p53 and pRb, and are thus implicated in the induction and maintenance of malignant cellular transformation. Indeed, antibodies against E6 and E7 of HPV16 and 18 have been found to be highly specific markers of cervical cancer in comparison to controls, [3][4][5] as well as of oropharyngeal cancer. [6][7][8][9][10] To date, little is known about the immune response to other HPV early proteins nor about the immune response to the E6 and E7 proteins of high-risk HPV types other than HPV16 and 18.…”
mentioning
confidence: 99%
“…The anti-E6 and anti-E7 antibodies have been identified as markers of CC. 11 , 14 16 The E4 protein binds to the cytoskeleton to promote the release of viral particles and assembles into stable amyloid-like fibers to finally accumulate in the lesion at different extents, depending on lesion grade. 17 In consequence, it has been suggested that the detection of E4 protein and/or antibodies against it in cervical biopsy tissues or serum can be markers for cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one prior study displayed the proteomes of multiple HPV types on slide-based protein microarrays, and Abs to E7 were the immunodominant response in cervical cancer patient sera [20]. In that study, Abs to E6 and L1, although previously reported [12,13,37], were not strongly detected, which may be attributable to the larger size of these proteins compared with E7, or the difficulties associated with expression, folding, and stability using E. coli for protein array generation. No significant difference was observed between seroreactivity of patients with precancerous lesions (HSIL) and healthy controls, but this needs to be confirmed using independent approaches.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to HPV infection, the development of HPV cancers is associated with IgG Abs, primarily to the oncogenic antigens E6 and E7, best studied for the most common subtype, HPV16. Serum Abs to HPV16 E6 and E7 proteins have been detected in sera of 30–40% of patients with invasive cervical cancer . Abs to HPV16 E6 and E7 were similarly detected in 30–50% of HPV‐positive OPC patients and Abs to E6 have been detected ten years before OPC diagnosis .…”
Section: Introductionmentioning
confidence: 98%